The Influence Of Entrepreneurial Orientation And Work Ethic On The Performance Of Disabled Entrepreneurs In Malang City - Nurhesti; Yuliati, Uci; Dewayani, Eka Kadharpa Utama (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The research aims to describe entrepreneurial orientation, work ethic and performance of disabled entrepreneurs in the city of Malang. The influence of entrepreneurial orientation on the performance of disabled entrepreneurs, the influence of work ethic on the performance of disabled entrepreneurs, knowing the influence of entrepreneurial orientation on work ethic, knowing the influence of entrepreneurial orientation and work ethic of people with disabilities. This research was conducted on entrepreneurs with 172 respondents. Sampling technique using simple random sampling, Data collection is carried out by interview techniques and questionnaires. Scale Range and Multiple Linear Regression data analysis techniques. Research shows entrepreneurial orientation in disabled entrepreneurs with strong criteria, work ethic in disabled entrepreneurs with very strong criteria, disabled entrepreneurial performance with very high criteria, Entrepreneurial orientation has a positive and significant effect on the performance of disabled entrepreneurs, work ethic has a positive and significant effect on the performance of disabled entrepreneurs, entrepreneurial orientatin has a positive and significant effect on entrepreneurial performance Disability, entrepreneurial orientation and work ethic have a positive and significant effect on the performance of disabled entrepreneurs.